PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 011 PEMATANG INDAH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Kesumawati, Kesumawati; Alim, Jesi Alexander; Alpusahri, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: This research aim to increase result of learning Mathematics class student of V SD Negeri 011 Pematang Indahacademic year 2014 / 2015. Research subjek class student of V SD Negeri 011 Pematang Indah with amount of student counted 14 students. Form this research of action class of collaborativewith two cycles. Research indicate that result learn upgrading student improvement, activity provision value learn first cycle of with average 64,58%. The second cycle of mount with average 89,58%. student activitythe first cycle with average 58,33%. The second cycle natural improvement of with average 83,33%. Result of natural research improvement of where before conducted action with model study of type cooperative of Make Match a complete elementary score only 4 peoples(28,57%) with average59,25. The first cyclemount completely reach 8 peoples(57,14%) with average ( 76,78). And the secound cycle of mount completely reach 14 people ( 100%) with average 90,71. So all of upgrading improvement of result learn in its entirety 53,09. Thereby can be concluded that hypothesis in this research " if applied model study of cooperative of tife Make Match a hence can improve result learn Mathematics class student of V SD Negeri 011 Pematang Indah" can be accepted.